Economic evaluation of pig rearing fed with different level of jaggery filter cake along with concentrate - PRASANNA S.B; RAVINDRA KUMAR, b.H.M. PATEL, SANJAY KUMAR (Indian Journal of Animal Production and Management, 2019)
The present study was carried out for economic evaluation of pig rearing fed with different levels of Jaggery filter cake along with concentrate. An experiment was designed using 30 Large White Yorkshire piglets (3 Â½ month old), randomly divided and maintained on 5 dietary treatment groups, viz. group I: concentrate only, group II: concentrate +250 g JFC, group III: concentrate +500 g JFC, group IV: concentrate +750 g JFC and group V: ad lib. JFC only. Jaggery filter cake supplementation was increased in the ratio of 50:100:150 g in group II, III, IV respectively, every fortnight during growing stage and every week during finishing stage. The cost of balanced ration was estimated by considering the prevailing prices of the feed ingredients, mineral salt, common salt and vitablend. The relative cost effectiveness of each diet was thus assessed. Further, the amount incurred for treatment of any disease outbreak was also included in the expenditure under different groups. By considering the total live weight gain under each treatment, the cost involved to produce 1 kg live weight gain was calculated. Net profit for each treatment was calculated separately by considering the sale price of pork produced at the end of experiment. The total cost during the whole experiment was highest in group I (no JFC), followed by group II, group IV and group III and lowest in group V (ad. lib JFC with no concentrate). Cost involved for production of 1 kg live weight for group I to V was Rs 35.25, 32.34, 29.48, 29.42 and 19.31, respectively. High cost incurred in group I was due to sole concentrate feeding and lowest cost in group V was due to sole feeding of JFC, respectively. Cost involved in group IV was marginally higher as compared to group III due to relatively more concentrate intake along with known quantity of JFC.